IMPROVING STUDENTS IN WRITING SKILL BY USING SCRAMBLED PICTURE IN NARRATIVE TEXT - Arum Yunita Puspitasari (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2018)
Writing is one of four basic skills that students in junior high school have to learn. While a writing is complicated because there are many aspects such as mechanics, vocabulary and grammar, and writing activities.The students must be able to combine word and sentences grammatically into written text. Based on junior high school curriculum which is designed by Indonesia government, the students should understand and create various functional texts, monologues and essays in the form of descriptive, procedure, report, recount and narrative text. The student should be able to develop their skill to express the meaning and the structure of the text. In this research the researcher founds some problem faced by the students in the eighth grade of SMP Islam Al Amin Malang. They don’t know how to start writing and organize their ideas. Second, they still had difficulties to understand conjunction and punctuation, third they were also low of vocabulary mastery. Beside that the teacher still used conventional technique to teach writing, especially in narrative text.The researchers used classroom action research. In this research, the researcher conducted one cycle in implementing the method by using Scrambled Picture. The researcher conducted in one cycle because in cycle one the criteria of success had been achieved. The success of this research is influenced by two factors; the researcher’s factor and the student’s factor. The researcher’s factor was the researcher’s classroom management and the researcher’s explanation. The students also happy to used Scrambled Picture in writing narrative text during teaching and learning process. Key Words: Improving, scramble, narattive